The Socio-Existential Anchors: The Case of the Future Expectations - Araujo-Kakiuchi, K (INST UNIV PESQUISAS RIO DE JANEIRO-IUPERJ, 2018)
The goal of this article is to discuss the work that individuals develop to sustain themselves in social life, focusing on the question of "socio-existential anchors", and in particular on one type of these: the expectations of the future. After a review of the theoretical debate and based on the results of a qualitative empirical research for the case of Chile, the text analyzes the way in which the figure of the going to the South-Field is constituted as the foundation of these expectations of the future and acts as an anchor for social existences. This analysis will allow to argue that the "socio-existential anchors" are active in specific individuals but are socially shared and can be understood as a response, with nuances according to social group, at once singular and general, to the structural requirements to which it is exposed at a certain historical moment.